العلامات الشعاعية للجزر المثاني الحالبي - فضة حاتم; قصاب إسلام ياسين; العلي محمود (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة عينة مكونة من 96 طفلاً راجعوا مشفى الأسد الجامعي في مدينة اللاذقية بإنتان بولي متكرر ومعند في الفترة الواقعة مابين 2007-2009 وبالاستقصاءات شُخِّص الجزر المثاني الحالبي عند27 طفلاً، يقسمون إلى 19 أنثى و8 ذكور وزعت الدراسة الإحصائية الإصابات حسب الجنس والعمر وجهة الإصابة والأعراض والعلامات المرافقة. أجري تصوير راجع للمثانة والإحليل أثناء التبول وتصوير ظليل للجهاز البولي بالحقن الوريدي وفحص بالأمواج فوق الصوتية لكل مريض. This study includes a sample of 96 patients who were admitted to the University Al-Assad Hospital in the period between 2007 and 2009 with urinary tract infection. Investigations revealed Vesicoureteric reflux (VUR) in 27 patients who were divided into 8 male cases and 19 female cases. A statistical study was made due to sex, age, the side of lesion and accompanied diseases. Every patient has undergone ultrasonography, micturating cystourethrography (MCUG) and intravenous urography (IVU).